Acute Effects on Blood Pressure Following Controlled Exposure to Cookstove Air Pollution in the STOVES Study. Issue 14 (16th July 2019) - Fedak, Kristen M.; Good, Nicholas; Walker, Ethan S.; Balmes, John; Brook, Robert D.; Clark, Maggie L.; Cole‐Hunter, Tom; Devlin, Robert; L'Orange, Christian; Luckasen, Gary; Mehaffy, John; Shelton, Rhiannon; et al.
Abstract : Background: Exposure to air pollution from solid fuel used in residential cookstoves is considered a leading environmental risk factor for disease globally, but evidence for this relationship is largely extrapolated from literature on smoking, secondhand smoke, and ambient fine particulate matter (PM2.5 ). Methods and Results: We conducted a controlled human‐exposure study (STOVES [the Subclinical Tests on Volunteers Exposed to Smoke] Study) to investigate acute responses in blood pressure following exposure to air pollution emissions from cookstove technologies. Forty‐eight healthy adults received 2‐hour exposures to 5 cookstove treatments (three stone fire, rocket elbow, fan rocket elbow, gasifier, and liquefied petroleum gas), spanning PM2.5 concentrations from 10 to 500 μg/m 3, and a filtered air control (0 μg/m 3 ). Thirty minutes after exposure, systolic pressure was lower for the three stone fire treatment (500 μg/m 3 PM2.5 ) compared with the control (−2.3 mm Hg; 95% CI, −4.5 to −0.1) and suggestively lower for the gasifier (35 μg/m 3 PM2.5 ; −1.8 mm Hg; 95% CI, −4.0 to 0.4). No differences were observed at 3 hours after exposure; however, at 24 hours after exposure, mean systolic pressure was 2 to 3 mm Hg higher for all treatments compared with control except for the rocket elbow stove. No differences were observed in diastolic pressure for any time point or treatment. Conclusions: Short‐term exposure to air pollution from cookstoves can elicit an increase in systolic pressure within 24 hours. This response occurred across a range of stove types and PM2.5 concentrations, raising concern that even low‐level exposures to cookstove air pollution may pose adverse cardiovascular effects.